1972
DOI: 10.3382/ps.0511707
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Accumulation and Hemorrhage in Livers of Laying Chickens.

Abstract: S. C. White Leghorn female chickens were subjected to a restricted-refeeding program in an attempt to induce fatty liver-hemorrhagic syndrome (FLHS) and to ascertain the relationship between hemorrhage occurrence and liver lipid content. Restricted feeding resulted in significantly (P< .01) lower liver, body and abdominal fat weights. The reduced liver weight reflected significantly (P<.01) lower water, lipid and non-lipid dry component weights. None of the hens on the restricted feeding schedules had any live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
1
2

Year Published

1978
1978
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 9 publications
0
47
1
2
Order By: Relevance
“…It has been suggested that excessive fat may disrupt liver morphology and result in weakening of the reticular framework and blood vessels in the liver (Riddell, 1997). Although it is possible that high hepatic fat content predisposes the hen to develop FLHS, equal or higher hepatic lipid content has been observed in birds without haemorrhage (Wolford and Polin, 1972;Squires and Leeson, 1988). Hence, the relationship between hepatic fat deposition and haemostatic lesions is not absolute.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been suggested that excessive fat may disrupt liver morphology and result in weakening of the reticular framework and blood vessels in the liver (Riddell, 1997). Although it is possible that high hepatic fat content predisposes the hen to develop FLHS, equal or higher hepatic lipid content has been observed in birds without haemorrhage (Wolford and Polin, 1972;Squires and Leeson, 1988). Hence, the relationship between hepatic fat deposition and haemostatic lesions is not absolute.…”
Section: Introductionmentioning
confidence: 96%
“…The decrease in egg production and increased mortality associated with FLHS cause considerable economic loss to egg producers (Riddell, 1997). Upon postmortem examination, the hens are found to have excess abdominal and liver fat and haemorrhages of various sizes in the liver (Wolford and Polin, 1972;Leeson et al, 1995;Riddell, 1997). It has been suggested that excessive fat may disrupt liver morphology and result in weakening of the reticular framework and blood vessels in the liver (Riddell, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…The liver is the major site for lipid synthesis and fatty liver haemorrhagic syndrome (FLHS) occurs with excess lipid accumulation in the liver (Wolford and Polin, 1972). This decreases egg production and leads to death under severe conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Certain traits have been associated with FLHS; a greater prevalence of FLHS was observed in heavier birds, taking the age and phase of production into consideration (Meijering, 1979). In addition, FLHS was associated with the presence of abdominal and liver fat in chicken (Wolford and Polin, 1972), while those with lower liver fat content remained unaffected (Wolford and Polin, 1972;Crespo and Shivaprasad, 2003). Yeh et al (2009) reported a positive correlation between FLHS and liver percentage (LP).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive hepatic lipid deposition in chicken can cause steatosis and fatty liver hemorrhagic syndrome (FLHS), which is characterized by obesity, an acute drop in egg production, and sudden death from hepatic rupture and hemorrhage (Wolford and Polin, 1972;Thomson et al, 2003;Yeh et al, 2009). Certain traits have been associated with FLHS; a greater prevalence of FLHS was observed in heavier birds, taking the age and phase of production into consideration (Meijering, 1979).…”
Section: Introductionmentioning
confidence: 99%